A lógica interna do jogo na escola: sistematização do conteúdo – o exemplo do basquetebol - Rosa, Anco Marcio Urach da (2022)
The sport is one of the greatest social phenomena of humanity, inserted in the various social fields and also an educational practice proposed in School Physical Education, is content provided in the Base National Common Curriculum (BNCC), a document that guides the systematized formation of the curricula of education systems and networks with the intention of giving equity to basic learning in the country's schools. The Military College of Santa Maria (CMSM) is part of a nationwide education network that follows the precepts of the Brazilian Army and its curricular guidelines. The Motor Praxiology (PM), theory of Motor Action, is recognized for its theoretical-scientific contribution, concepts and terminologies related to Body Practices. The themes: Sport, Physical Education, BNCC, CMSM and Motor Praxiology correspond the first stage to delimit systematization in search of research results, to fulfill a second moment a Praxiological Analysis of basketball was performed, based on the Universals of sports game of Parlebas, emphasizing the Roles and Subroles of the modality, in a third moment to meet the didactic and pedagogical aspects are referenced to the perspective of Pedagogy of Motor Conducts, designed by Parlebas for Physical Education and the Didactic Situation from the perspective of a praxiological system. Regarding the methodological aspect, the research is based on the assumptions of a theoretical research, with the use of qualitative data based on surveys of bibliographic references. The research aims to elaborate and evidence concepts of Motor Praxiology for the systematization of the content of Physical Education/basketball of the Military College of Santa Maria in the light of praxiological theory. To achieve the general objective, the following specific objectives were defined: Presenting the official documents, BNCC and Pedagogical Project of the CMSM, and proposal for the teaching of invasion sports in school; Present and justify the concepts of Motor Praxiology that will contribute to the systematization of contents for the teaching of Invasion sports in the CMSM, in view of the characterization of the Internal Logic of Basketball and; To highlight the contributions of Motor Praxiology to the didactic elements of Physical Education in the CMSM. We observed the relevance of the criteria of praxiological theory for the organization of Body Practices from their systemic character, as well as the perspective of a School Physical Education focused on the education of the Motor Conducts of students.